New directions for ASEAN - Desker, Barry (2011)
As ASEAN foreign ministers prepare for their annual meetings next month in Hanoi, a number of key issues await to be resolved. Can the ministers preserve the ASEAN model of community building amidst the emergence of alternative approaches?